If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = 6x + 31 Reorder the terms: 5x = 31 + 6x Solving 5x = 31 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5x + -6x = 31 + 6x + -6x Combine like terms: 5x + -6x = -1x -1x = 31 + 6x + -6x Combine like terms: 6x + -6x = 0 -1x = 31 + 0 -1x = 31 Divide each side by '-1'. x = -31 Simplifying x = -31
| 25.00x=4.50 | | 3y-2+6x=0 | | 2x-6=3x+1-x-2 | | 4x^2+4x=9 | | 2(x+4)-5=2x+13 | | n+5=9+2n-3-8 | | .5(4x-10)=52+3x | | 69=3v | | 3x-6+x+8=42 | | 5xy^2+3xy^2= | | -5w^2+23w-42=0 | | 11=4x-3y | | 0=-16t^2+50t+6 | | 5x-4=3x+2x+3-2+1 | | 72=5c+7c-2c | | n+5=-1-16 | | 2(-3a+5)=2y+3 | | 68=4v | | a(a^7+1)-7(a^7+1)=0 | | 4x-3=x-3+3x | | 3(4)-6+4+8=42 | | m+5=1 | | 12x-7=27x+3 | | -1x=13 | | 34a-4(5d+2)=36 | | 235=177-x | | -5n-15n=10 | | 6x-2=4x-(-2x+2) | | J=9(3.14)p | | 3x-3=2x-16 | | -5n-n=10 | | 3x-2=16-x^2 |